Exploring Digital Marketing Strategies toward Inbound-Outbound Techniques: A Qualitative Analysis of Turkish Startups - Sahin, Begum (Universitas Negeri Semarang, 2021)
Startups often fail due to the lack of successful marketing strategies as it directly effects their business growth. This paper aims to explore the awareness and the propensity of digital marketing approach in technology-oriented entrepreneurship toward inbound-outbound marketing techniques. In this regard, a qualitative analysis is adopted to two selected startups through case studies. Data is collected by in-dept interviews and documentary analysis is used considering qualitative nature. The results are presented toward content analysis as data-treatment technique. The empirical evidence obtained identifies that the digital marketing implemented by startups is quite low, moreover, the importance and the advantages like running cost and customer value creation are not recognized yet. The study also releases that traditional marketing is preferred within digital marketing and traditional marketing feeds and even captures both inbound and outbound marketing techniques. The contribution of this study is to propose an integrative and holistic model for entrepreneurs with the combination of traditional and digital marketing approach. The model can be accepted as a useful tool to improve the marketing management competencies of startups and guide the marketing activities concurrently.